Nathaniel Benchley - Unknown:::Creator::::::::::::
Four poses of humorist and Steinbeck friend Nathaniel Benchley. Taken at the same time as the photograph strip of Gwyn Steinbeck, number 0-020. Original is in the safe (in strip).